Methodology for integrating flexibility into realistic large-scale distribution network planning - Ulrich Ziegler, David; Prettico, Giuseppe; Mateo Domingo, Carlos; Gómez San Román, Tomás (My University, 2023)
Este trabajo propone una metodología para optimizar los planes de expansión de la red de distribución, mediante una herramienta de planificación de la red de distribución de una sola etapa, utilizando tanto activos convencionales como contratos de flexibilidad. Se ha implementado un algoritmo de búsqueda metaheurística, llamado Tabu Search, para resolver el problema de optimización. Los resultados muestran que, en el caso analizado, el uso de la flexibilidad en combinación con refuerzos convencionales permite reducir el coste total de expansión de la red en aproximadamente un 1 %.

This paper proposes a methodology to obtain cost optimal distribution network expansion plans, by modelling a single-stage distribution network planning tool, using conventional assets as well as flexibility contracts. A Tabu Search metaheuristic has been implemented in order to solve the optimization problem. A case study based on a realistic large-scale city network model is presented, for a planning horizon of ten years with significant load growth due to electromobility penetration. Results show that, in the analysed case study, the use of flexibility in combination with conventional reinforcements can reduce the total expansion network cost by about 1 %. Furthermore, a sensitivity analysis on the cost of flexibility contracting is undertaken. Remarkably, the presented methodology generalises to further alternative solutions by providing a straightforward financial benchmark between the later and conventional grid expansion.